METAPHORICAL REPRESENTATION OF EMOTIONS AND THOUGHT PROCESSES IN AN ENGLISH-LANGUAGE LITERARY TEXT - Tumparova, Guzal (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The article examines the role of metaphor as a cognitive mechanism for representing a person's inner world in English literary texts. Drawing on the conceptual position of cognitive linguistics, formulated by G. Lakoff and M. Johnson, that the everyday conceptual system through which the world is pecieved and understood is inherently metaphorical, the author emphasizes that metaphor is not merely a stylistic device, but one of the key tools for conceptualizing emotions, thought processes, subjective states, and understanding them through the creation of a literary image. Using specific examples of metaphors expressing emotions and thought processes, the text illustrates how emotional impact on the reader is achieved in a literary work, allowing them to feel the psychological states of the characters. It is concluded that by using metaphors in literary discourse, writers shape readers' mental models of perceiving the inner world of characters, their emotions, thereby fostering psychological empathy and interactions between the characters and the reader. Metaphors serve interconnected functions – cognitive, esthetic, and empathetic. Cognitive function is manifested in the structuring and understanding of emotions and thought processes; esthetic function gives the text expressiveness and imagery; and empathic function facilitates the establishment of an emotional connection between the reader and the character. The analysis of metaphorical constructions presented in the article shows that cognitive and emotional processes are embodied in literary form through metaphor, become understandable, and evoke an emotional response in the reader, making the hero's inner world vivid and psychologically authentic. Thus, metaphor is considered a crucial tool for creating an artistic image and expressing a person's emotional and psychological state.
Keywords: cognitive linguistics; literary text; metaphor; inner world; emotions; thought processes; mental models